Human Rights and Public Health in the AIDS Pandemic. - Gostin, Lawrence O. (Oxford University Press, USA, 1997)
Foreword. Jose Ayala Lasso, UN High Commissioner for Human Rights, and Peter Piot, Executive Director, UNAIDS1. International Human Rights Law in the AIDS Pandemic2. Harmonizing Human Rights and Public Health3. Human Rights Impact Assessment4. AIDS Policies and Practices: Integrating Public Health Benefits and Human Rights5. Case Studies Raising Critical Questions in HIV Policy and Research: Balancing Public Health Benefits and Human Rights Burdens.